2015
DOI: 10.1136/bcr-2015-209411
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of chronic high-output ileostomy with high dose loperamide

Abstract: High-stoma output is a common problem that can lead to dehydration and electrolyte disturbance. The following report describes three patients with end ileostomy who had high-stoma outputs where conventional medical management was unsuccessful in controlling stoma output. All three patients responded to high-dose loperamide, resulting in significant clinical improvement. High-dose loperamide therapy should be considered in patients with high-stoma output who have failed conventional medical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The routine dosage of loperamide is 20 mg twice daily by mouth, but the dosage can be increased if it is not effective. Alicia Mackowski reported that increasing the dosage of loperamide to 30 mg per day in individual patients can reduce the amount of stoma excretion, without observed abnormality in renal function [ 20 ]. Unfortunately, we cannot record the specific time of HOS patients’ return and only make a classification based on 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The routine dosage of loperamide is 20 mg twice daily by mouth, but the dosage can be increased if it is not effective. Alicia Mackowski reported that increasing the dosage of loperamide to 30 mg per day in individual patients can reduce the amount of stoma excretion, without observed abnormality in renal function [ 20 ]. Unfortunately, we cannot record the specific time of HOS patients’ return and only make a classification based on 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Routine dosage of loperamide is 20 mg twice daily by mouth, but dosage can be increased if not effective. Alicia Mackowski reported that increasing the dosage of loperamide to 300 mg per day in individual patients can reduce the amount of stoma excretion, without observed abnormality in renal function [18].…”
Section: Discussionmentioning
confidence: 99%
“…Mackowski reported that increasing the dosage of loperamide to 300 mg per day in individual patients can reduce the amount of stoma excretion, without observed abnormality in renal function [18].…”
Section: Discussionmentioning
confidence: 99%